Khusr in the Perspective of the Qur'an: Transformation of Meaning from Worldly Loss to Spiritual Loss - Maghfiroh, Nala Hanifatul; Solihin; Syuaib, Ibrahim (Quranic and Tafsir studies Programme at Ushuluddin Faculty, 2025)
The term khusr in modern human thought is often understood in material terms, such as financial loss or business failure. However, in the Qur'an, all forms of khusran (loss) primarily refer to spiritual and existential dimensions. This study aims to explore the meaning of khusr in the Qur'an using a qualitative approach based on Toshihiko Izutsu's semantic analysis. By examining the relational meaning of khusr in the pre-Qur'anic period through pre-Islamic Arabic poetry, the concept of loss is shown in the context of warfare and tribal social life. For example, in the poetry of Ka'ab bin Zuhair, khusr signifies destruction and misguidance. During the Qur'anic era, khusr frequently appears as an ism fā’il (active participle) indicating those who experience loss due to human misconduct, such as disbelief, deceit, oppression, misguidance, and futile deeds. In the post-Qur'anic period, the meaning of khusr remained consistent with this spiritual understanding, although its usage gradually expanded toward more material aspects of life.